Relationship between strength characteristics and unweighted and weighted vertical jump height - Kraska, J. M.; Ramsey, M. W.; Haff, G. G.; Fethke, N.; Sands, W. A.; Stone, M. E.; Stone, M. H. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To investigate the relationship between maximum strength and differences in jump height during weighted and unweighted (body weight) static (SJ) and countermovement jumps (CMJ). Methods: Sixty-three collegiate athletes (mean ± SD; age= 19.9 ± 1.3 y; body mass = 72.9 ± 19.6 kg; height = 172.8 ± 7.7 cm) performed two trials of the SJ and CMJ with 0 kg and 20 kg on a force plate; and two trials of mid-thigh isometric clean pulls in a custom rack over a force plate (1000-Hz sampling). Jump height (JH) was calculated from flight time. Force-time curve analyses determined the following: isometric peak force (IPF), isometric force (IF) at 50, 90, and 250 ms, and isometric rates of force development (IRFD). Absolute and allometric scaled forces, [absolute force/(body mass0.67)], were used in correlations. Results: IPF, IRFD, F50a, F50, F90, and F250 showed moderate/strong correlations with SJ and CMJ height percent decrease from 0 to 20 kg. IPFa and F250a showed weak/moderate correlations with percent height decrease. Comparing strongest (n = 6) to weakest (n = 6): t tests revealed that stronger athletes (IPFa) performed superior to weaker athletes. Conclusion: Data indicate the ability to produce higher peak and instantaneous forces and IRFD is related to JH and to smaller differences between weighted and unweighted jump heights. Stronger athletes jump higher and show smaller decrements in JH with load. A weighted jump may be a practical method of assessing relative strength levels.